Cartografia de afetos: as narrativas orais de sete mulheres em comunidades tradicionais nas/das Amazônias da região Bragantina, no Pará - Maria, João Leno Pereira de (2023)
This thesis is situated at the intersection of Gender Studies, Poetics of Orality, and Decoloniality. It focuses on the representations of femininity and its traditional knowledge, which have long been debated in academic settings and various social contexts. Considering women in their processes/experiences has constituted a potent political and scientific discourse in the XX and XXI centuries. Thus, this text examines the oral narratives of seven women from traditional communities in the Amazonas region of the city of Bragança (located in the state of Pará, Brazil), interpreting them and their stories through categories such as intersectionality (AKOTIRENE, 2019), identity and personal/collective memory (RICOEUR, 2000), (HALBWACHS, 2013), and traces (GAGNEBIN, 2006). The chosen methodological approach will be cartography, acknowledging the plurality and fluidity in our fieldwork and the voices of the interviewees, which prompted us to reconsider our epistemological choices and contemplate the feasibility of a thesis engaged in a dialogue with popular religiosities, traditional knowledge, and female agency. As an academic contribution, I introduce and delve into the concepts of Proto-ambientation and Identitary Path, aiming to broaden the debate on ethics in fieldwork in traditional communities and, simultaneously, engage in an exercise of (co)creation based on my listening, thus offering a more fitting concept for the shared experiences. Additionally, we will draw on the theoretical support of authors such as (MONTENEGRO,1994; PERROT, 1989; GEERTZ, 1978; DURAN, 1997; MAUSS, 2003), among others.